The Impact of Leadership Styles and Leader Satisfaction on Turnover Intention of Chinese Employees under 35 in Software and Technology Development Enterprises - Li, Ziyu (2022)
Software and technology development enterprises in China are knowledge-intensive industries, and their rapid development cannot be achieved without excellent human resources. In such enterprises, employees over 35 years of age who have not yet attained their core rank may be laid off and employees under 35 years of age are recruited to maintain the youthful atmosphere and vitality of the enterprise. However, the number of employees under the age of 35 leaving voluntarily has been increasing in recent years, which is costing the company a lot of money and posing a risk. It is therefore essential for enterprises to understand their employees' intention to leave and the reasons why. In work situations, employees usually spend the most time with their leaders, and it can be argued that employees' work emotions are largely influenced by their leadership behaviour and style. In China, however, there is a significant vacuum in the research on the connection between leadership style and employee leader satisfaction and turnover intentions. Therefore, this paper collects data in the form of a quantitative study and a structured questionnaire in order to help companies reduce the problem and fill the gaps in Chinese research. A structural equation model was also used to analyse the relationship between turnover intentions, leader satisfaction and leadership styles of Chinese employees under the age of 35 in software and technology development enterprises. The final analysis of the 340 valid samples demonstrated a negative association between transformational/ transactional leadership style and turnover intentions, and a positive relationship with leader satisfaction. Leader satisfaction also affects employees' intention to leave, and is negatively related to it. Finally, this study also provides some feasible suggestions for software and technology development enterprises in China, which have some practical implications.